Exosomes-derived miR-548am-5p promotes colorectal cancer progression: miR-548am-5p promotes CRC - Li, Fangfang; Zhang, Minglei; Yin, Xiaodong; Zhang, Wei; Li, Haiyang; Gao, Chao (Cellular and Molecular Biology, 2023)
Exosomes are vital modulators in intercellular communication and microRNAs (miRNAs) are enriched within exosomes. MiRNAs are important participants in affecting colorectal cancer (CRC) progression, but the influence and latent mechanism of cancer-secreted exosomal miRNAs in colorectal cancer are not fully understood. miR-548am-5p has been reported to be differentially expressed in colon cancer and is indicated as a biomarker for colon cancer diagnosis at the early stage. In this study, we aimed to explore the role of exosomes-derived miR-548am-5p in CRC development. ISH and FISH were implemented to assess miR-548am-5p expression and location in CRC. CRC cells-secreted exosomes were identified via transmission electron microscopy and western blot. Colony formation, sphere formation and flow cytometry assessed the changes in proliferation, stemness and apoptosis of CRC cells. Bioinformatic analyses and mechanical experiments verified the binding of miR-548am-5p and RAR-related orphan receptor A (RORA). Our study identified miR-548am-5p was highly expressed in CRC tissues and cells. Tumor-derived exosomes expedited CRC cell proliferation and stemness along with secreted miR-548am-5p. Moreover, miR-548am-5p inhibition suppressed CRC cell proliferation and stemness while promoting cell apoptosis. RORA was the target mRNA of miR-548am-5p. Down-regulation of RORA was discovered in CRC and its expression was repressed by CRC cell-derived exosomes. As a result, our work elucidated that tumor-derived exosomal miR-548am-5p promoted CRC cell proliferation and stemness via targeting RORA, providing a valuable sight for CRC therapy.